2002
DOI: 10.1212/wnl.58.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, expenditures, utilization, and payment for persons with MS in insured populations

Abstract: Insured enrollees with MS are two to three times more expensive than average insured enrollees. If the premiums that employers or governments pay health insurers and the capitation amounts that insurers pay health care providers do not account for these higher costs, a disincentive is created for the enrollment and care of persons with MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
35
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 15 publications
1
35
1
Order By: Relevance
“…19 The annual rates of MS prevalence derived from our study population are similar to those reported by Pope et al, 6 using 2 years of claims data. Pope' s prevalence rates were slightly lower for the 55 to 64 years age group (26/10,000 in Pope compared to 32/10,000 here).…”
Section: ■■ Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…19 The annual rates of MS prevalence derived from our study population are similar to those reported by Pope et al, 6 using 2 years of claims data. Pope' s prevalence rates were slightly lower for the 55 to 64 years age group (26/10,000 in Pope compared to 32/10,000 here).…”
Section: ■■ Discussionsupporting
confidence: 86%
“…Pope' s prevalence rates were slightly lower for the 55 to 64 years age group (26/10,000 in Pope compared to 32/10,000 here). 6 We surmise that an increased percentage of females or a higher concentration of members aged 35 to 54 years would increase estimates of the potential population of users. Accordingly, we would anticipate budget impact to be higher in these scenarios as well.…”
Section: ■■ Discussionmentioning
confidence: 94%
“…One of the most promising approaches to fair compensation for the medical care of MS may be supplementing this strategy with functional status measures, if possible. Pope et al (2002) found that costs were 2-3 times higher for insured enrollees with MS compared with average insured members. 51 For example, calculated annual all-cause medical expenditures were estimated as $7,677 per privately insured enrollee with MS versus $2,394 for all privately insured enrollees, $13,048 per Medicare beneficiary with MS compared with $6,006 for all Medicare beneficiaries, and $7,352 per Medicaid disabled recipient with MS versus $4,088 per disabled recipient without MS.…”
mentioning
confidence: 98%
“…Pope et al (2002) found that costs were 2-3 times higher for insured enrollees with MS compared with average insured members. 51 For example, calculated annual all-cause medical expenditures were estimated as $7,677 per privately insured enrollee with MS versus $2,394 for all privately insured enrollees, $13,048 per Medicare beneficiary with MS compared with $6,006 for all Medicare beneficiaries, and $7,352 per Medicaid disabled recipient with MS versus $4,088 per disabled recipient without MS. The results of this analysis identified 2 important implications: (a) despite the tendency to under-identify persons with MS in claims data, MS prevalence rates are actually higher than anticipated; and (b) MS patient access to care and appropriate capitated payment levels to care providers must be adequate.…”
mentioning
confidence: 98%
See 1 more Smart Citation